ANALISIS PENGARUH KEHALUSAN ABU TERBANG (ABU SEKAM PADI) TERHADAP STABILITAS DAN KEPADATAN AC-BCNR - Farlin Rosyad; Dedek Adriyansah; Irham Irham; Wahyuni Wahab (Rang Teknik Journal, 2024)
The road is an infrastructure that plays an essential role in the development of a region which is a connection between one region and another. The concrete asphalt layer (laston) is the most commonly used road violence in the Indonesian region consisting of asphalt, aggregate and filler. In an effort to add substitutes of fine material that can be used as a material in asphalt mixture, then easy-toobtained rice husk ash are used in research as an alternative to fine material in asphalt mixture. The asphalt used in this research is the rubber asphalt sir 20 (Standard Indonesian Rubber) which is derived from PT. MBS (Modifikasi Bitumen Sumatera). This research was conducted with the aim of knowing the optimum value of the mixture rice husk ash as a fine material replacement against AC-BCNR coated laston and to find out how much the effect of the smoothness of rice husk ash as a fine material replacement against AC-BCNR coated laston is reviewed from stability and density. The percentage of rice husk ash used in this research is 4 %, 6 % and 8 % for zone 0, Zone 1, Zone 2 as well as zone 3 as substitution of fine materials in a mix of AC-BCNR and normal test objects without rice husk ash. The research used marshall testing methods by reviewing the effects of rice husk ash on the value of stability and density. Based on the results of testing the marshall parameter, reviewed by the variety of zones and the percentage of the level of substitution of rice husk ash it can be concluded that the optimum value of the use of the rate of rice husk ash exists in the zone 2 percentage 4 %. Marshall standard optimum stability value is located in zone 2 percentage 4 % by 1301 kg while in zone 2 percentage 6 % there is a drop back to 1285.6 kg. Optimum density value (bulk density) lies in zone 2 percentage 4 % of 2,297 gr/cc whereas in zone 2 percentage 6 % there is a drop back to 2,291 gr/cc.Keyword: Rice husk ash, Rubber asphalt, AC-BCNR, Stability, Density